Property evaluation for residential structures: A predictive approach using view and spatial attributes. - Abdelalim, Amro; Ismail, Ayman (Springer, 2018)
Computational simulation programs and analytical scientific methods are usually used to evaluate properties and structures in the city. Although such programs can help gather various information and analyze it better and more accurately than with manual methods, they usually require a huge amount of historical data on sale prices and also extensive property data. This may be somewhat complicated in developing countries where the history of sales may be hard to track for various reasons. This paper is an attempt to abstract that process by investigating the relationship between property value for residential structures and both building overlook and its spatial attributes as two of the primary factors affecting property value. Property value is considered as a collective lump-sum indication of residential privileges. Spatial and view attributes are two of the main privileges which will be studied. The paper uses Space Syntax as an analytical tool for comparing the influence of each of these attributes using regression analysis.
Keywords: Immobilienmarkt; Grundstücksbewertung; Grundsteuer; Regressionsanalyse